DESIGN OF SOLAR TRACKING SYSTEM TO IMPROVE SOLAR ENERGY ABSORPTION BASED ON Arduino UNO - Teguh Setiadi; Benny Setyo Hartomo (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2022)
This study aims to create a tool to increase the energy absorption of arduino uno-based solar panels to generate current, voltage, and radiation intensity data that will be used to monitor solar power plants automatically using the Waterfall method. Connecting the sensor with the arduino uno, the design of the arduino uno-based solar panel works well in detecting the temperature and humidity of the room. The results of the PIR Sensor Range Angle are carried out horizontally to the sensor and the distance is also varied from 1 m to 7 m. The test results of the DHT11 Sensor were tested for accuracy of measurements using a humidity comparison/thermometer type k Lutron HT-3006HA which has the ability to measure temperature and humidity. The data obtained is calculated the value of 0% error. LDR sensor testing is done by exposing the sensor directly to the state of natural light in the room from time to time with normal weather conditions. Where all detected ADC values are above 500 so the lights are on.